Designing an Used Goods Donation System to Reduce Waste Accumulation Using the WASPAS Method - Wayahdi, M. Rhifky; Ruziq, Fahmi (Sinkron : jurnal dan penelitian teknik informatika, 2024)
This research aims to build a website application-based selection system for recipients of used goods donations using the WASPAS method. This system is designed to assist in the efficient and fair distribution of used goods to recipients in need. The WASPAS method is applied to calculate the preference value (Qi) for each alternative donation recipient based on predetermined criteria. The analysis results show that "Alternative-01" is the best alternative with the highest Qi value (1.866), while "Alternative-02" has the lowest Qi value (1.713). The significant difference in Qi values ​​between these two alternatives indicates a clear difference in preferences. The weight (w) given to each criterion plays an important role in forming the preference value (Qi). Therefore, careful consideration needs to be taken in determining the weight of each criterion to ensure that the final decision is in line with expectations. The WASPAS method has proven to be effective in the selection system for recipients of used goods donations. The advantage of this method lies in its ability to handle multi-criteria problems and uncertain data. By applying the WASPAS method, the decision-making process can be carried out more quickly, accurately and objectively. Although the WASPAS method provides a strong basis for decision making, it is also necessary to consider other relevant factors, both quantitative and qualitative. This will ensure that the final decision taken is the best decision and in accordance with the research objectives.